Postawy nauczycieli akademickich wobec pracy dydaktycznej jako składnik współczesnej kultury akademickiej = Academic teachers` attitudes toward didactics work as a component of contemporary academic culture - Borucka, Ewelina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article addresses the issue of academic teachers` attitudes toward didactic work as a crucial component of contemporary academic culture, placing them within the context of a broader theoretical framework related to organizational culture. The aim of the article is to show the relationship between academic teachers` attitudes towards teaching and their individual satisfaction with their work and the quality of teacher-student relations.
Keywords: academic culture; attitudes towards didactic work; organizational culture; kultura akademicka; postawy wobec pracy dydaktycznej; kultura organizacyjna